2021
DOI: 10.1016/j.jddst.2021.102592
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of alkaline phosphatase enzymatic activity after electrospinning and electrospraying

Abstract: The high target specificity and multifunctionality of proteins has led to great interest in their clinical use. To this end, the development of delivery systems capable of preserving their bioactivity and improving bioavailability is pivotal to achieve high effectiveness and satisfactory therapeutic outcomes. Electrohydrodynamic (EHD) techniques, namely electrospinning and electrospraying, have been widely explored for protein encapsulation and delivery. In this work, monoaxial and coaxial electrospinning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 67 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…The ALP activity for the 24 h culture period shows that the modified nanofiber membrane has higher activity by normalizing the DNA of MG-63 cells at 170.74 U/L. The ALP activity of the modified nanofiber membrane is 54.99% higher than that of the bare membrane. , This remarkable increase in mineralization is due to the incorporation of MgO/gC 3 N 4 nanocomposites into PAN/PEG. Also, the PEG rich in OH groups can initiate the increase of viability in cells.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ALP activity for the 24 h culture period shows that the modified nanofiber membrane has higher activity by normalizing the DNA of MG-63 cells at 170.74 U/L. The ALP activity of the modified nanofiber membrane is 54.99% higher than that of the bare membrane. , This remarkable increase in mineralization is due to the incorporation of MgO/gC 3 N 4 nanocomposites into PAN/PEG. Also, the PEG rich in OH groups can initiate the increase of viability in cells.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The ALP activity of the modified nanofiber membrane is 54.99% higher than that of the bare membrane. 49,50 This remarkable increase in mineralization is due to the incorporation of MgO/gC 3 N 4 nanocomposites into PAN/PEG. Also, the PEG rich in OH groups can initiate the increase of viability in cells.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Monoaxial or blend EHD is achieved from a single solution where all components are mixed, whereas with co-axial EHD, a two-needle spinneret allows the production of core–shell structures from two separated solutions. Thus, with co-axial EHD, biomolecules can be protected from potential solvent induced denaturation and loss of function minimised, whereas the blend process often leads to denaturation and loss in bioactivity due to the harsh environment (e.g., organic solvents) [ 20 , 21 ]. However, co-axial EHD is more complex compared with the blend process, making it more challenging to scale up [ 3 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with co-axial EHD, biomolecules can be protected from potential solvent induced denaturation and loss of function minimised, whereas the blend process often leads to denaturation and loss in bioactivity due to the harsh environment (e.g., organic solvents) [ 20 , 21 ]. However, co-axial EHD is more complex compared with the blend process, making it more challenging to scale up [ 3 , 20 ]. Onyekuru et al have shown that proteins such as alkaline phosphatase can be processed by EHD into fibres and particles without loss of activity, even for blend solutions [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation